Pemanfaatan Bioteknologi pada Pembuatan Makanan Probiotik Yoghurt yang Halalan Thayyiban - Nurul Fajriana; Ulia Hanum; Qurratu Aini; Cut Novrita Rizki; Meutia Zahara; Suwarniati Suwarniati; Mauizah Hasanah; Fatemah Rosma; Manja Manja; Nurhidayatun Rahma (I-Com: Indonesian Community Journal, 2024)
ABSTRACT The creation of probiotic food/drinks emerged from awareness of the importance of public health and the role of probiotics in improving the balance of the gut microbiota. In this context, probiotics provide significant benefits for the digestive and immune systems. However, there are still many people who do not know the benefits of probiotics and how to include them in their daily diet. Therefore, through this outreach activity, it is hoped that it can increase public understanding about probiotics and provide practical skills in making probiotic food/drinks at home. The methods used in PkM activities are lectures/presentation of material, demonstrations, discussions and presentations. Several steps in the process of making yoghurt, namely: (1) Selection of raw materials, (2) Heating the milk, (3) Cooling the milk, (4) Adding starter culture, (5) Fermentation for 8-12 hours, (6) Cooling and storage. It should be noted that variations in raw materials, methods and types of lactic acid bacteria used can produce yoghurt with different characteristics. Therefore, the process of making yoghurt in this PKM activity meets halalan thayyiban standards.